SPECIAL PHYSICAL TRAINING FOR VOLLEYBALL PLAYERS AT THE FIRST STAGE OF TRAINING - Sulaymanov Qurbanali; Redjapov O’tkir (Journals Park Publishing, 2023)
A volleyball player at the stage of specialization must have good speed training. This is expressed in running qualities. Running makes high demands on the athlete, he must have excellent physical fitness, be strong, fast, well-coordinated.
Keywords: Sports specialization, catalog of jumping exercises, jumping training program, jumping training, special exercises, speed abilities, speed training of volleyball players, speed-strength qualities.